Cost analysis of pico hydro turbine for power production - Basar, Mohd Farriz; Mohamad Sapiee, Mohd Razali; Rahman, Syukri; Hamdan, Zulfiqah; Borhan, Shuhada; Sopian, Kamaruzzaman (AENSI Publisher, 2014)
Background: Turbine played a significant role in the hydro system and a determinant of the quality and quantity production of electric power in each power system. Objective: In this paper, several types of pico hydro water turbines are reviewed and compared. The water head, water flow rate and the current market price are the basic aspects considered in discussing the turbines selection. Results: Most of the small hydro turbines currently available are mostly suitable for low head high flow or high head low flow condition. By the assumption that the percentage of turbine efficiency is consistent for all conditions of water resources, the ability of water turbine to produce high output during low head low flow condition is low. Conclusion: The effectiveness of a turbine does not only depends on the productivity of the turbine to generate output power, but must also be seen in terms of cost and economical investment.